An Analysis of Students’ Difficulties in Translating Idiomatic Expressions: What and Why? - Zahratul Idami; Shafrida Wati; Riqqah Balqis (Universitas Muhammadiyah Kalimantan Timur, 2022)
This study analyzed students’ difficulties in translating idiomatic expression sentences at the sixth semester of English department of IAIN Langsa. It further discussed factors that trigger the problems. The research applied qualitative content analysis approach and the subject was 10 students of the sixth-semester of English education department, IAIN Langsa. Data collecting techniques were tests and interviews. The findings showed that the learners experienced several difficulties in translating idiomatic expressions included lexical knowledge, cultural differences, and stylistic barrier. These were due to the difficulty in finding the closest equivalent source language and the difficulty in finding meaning that matches the meaning of the idiomatic expressions. The factors that generated those difficulties included students' lack of knowledge of idiomatic expressions, cultural differences between English and Indonesian, students rarely used them in speaking or writing in everyday life, and the difficulty in interpreting idiomatic expressions. However, this study contributed to encourage both lecturers and students to emphasize vocabulary enhancement and language expressions, especially idioms, and to practice them in writing and speaking both in and outside of the classroom.